1999
DOI: 10.1038/sj.cdd.4400473
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of phosphatidylserine is a general feature in the phagocytosis of apoptotic lymphocytes by macrophages

Abstract: Although different macrophages exploit different cell surface receptors to recognize apoptotic lymphocytes, indirect evidence suggested that the phosphatidylserine (PS) that appears on the surface of lymphocytes undergoing apoptosis participates in specific recognition by all types of macrophages. To test this possibility directly, annexin V, a protein that specifically binds to PS, was used to mask this phospholipid on the apoptotic cell surface. Preincubation of apoptotic lymphocytes with annexin V blocked p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
164
2
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(173 citation statements)
references
References 18 publications
4
164
2
3
Order By: Relevance
“…The redundancy of receptors involved in this process makes it difficult to identify the dominant receptors and/or block the uptake process on the plasma membrane. Although it is thought that all these receptors may, in part, recognize externalized PS on the surface of apoptotic bodies Hoffmann et al, 2001;Krahling et al, 1999), this has not been conclusively demonstrated. Thus, the PS-R is the best characterized in regard to its ability to recognize PS on the surface of the apoptotic body/cell.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The redundancy of receptors involved in this process makes it difficult to identify the dominant receptors and/or block the uptake process on the plasma membrane. Although it is thought that all these receptors may, in part, recognize externalized PS on the surface of apoptotic bodies Hoffmann et al, 2001;Krahling et al, 1999), this has not been conclusively demonstrated. Thus, the PS-R is the best characterized in regard to its ability to recognize PS on the surface of the apoptotic body/cell.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that, as in macrophages, microtubules are involved in the engulfment of apoptotic bodies by stellate cells (Fadok and Chimini, 2001;Krahling et al, 1999). More importantly, nocodazole provided a tool to examine the importance of apoptotic body engulfment in COLIA1 and TGF-␤1 generation by the stellate cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Blockade of apoptotic cell engulfment can be affected by the masking of PS through the pre-binding of annexin V to exposed PS on the apoptotic cell surface. 9 Immune pathologies attributed to the failure to promptly clear apoptotic cells, especially including chronic inflammation and autoimmunity characteristic of systemic lupus erythematosus and rheumatic diseases (see Savill et al 6 and Birge et al 8 and citations therein) may rather reflect deficiencies in apoptotic cell interactions and IAI.…”
Section: Open Questionsmentioning
confidence: 99%